(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
Airports are a part of the world transportation network. Huge investments are made annually for airport pavement construction, maintenances and rehabilitations. The idea of integrating life-cycle cost analysis (LCCA) and life cycle assessment (LCA) is the latest approach to develop a method for assessing pavement sustainability. In this regard, research on economic evaluation analysis methods has resulted in the development and improvement of pavement management systems (PMS). This paper compares two main economic evaluations which mainly could use in LCCA namely net future value (NFV) and net present Value (NPV). To indicate the effect of economic evaluation a case study is examined. In this research LCCA comprises three main components which are direct costs, indirect costs, and salvage value. Airport Revenue Reduction Cost (ARRC) and Airline Delay Cost (ADC) considered as two specific indirect/user costs. The results show the impact of different economic analysis method on project decision-making where the use of crack sealing overlay (CSOL) is 35.8% and 28.3% more cost-effective than Portland cement concrete (PCC) and hot-mix asphalt (HMA), respectively.